2020
DOI: 10.3390/molecules25122790
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Photophore-Containing Lactisole Derivatives to Elucidate Sweet Taste Receptors

Abstract: Lactisole, which has a 2-phenoxy propionic acid skeleton, is well-known as an inhibitor of sweet taste receptors. We recently revealed some of the structure–activity relationships of the aromatic ring and chiral center of lactisole. Photoaffinity labeling is one of the common chemical biology methods to elucidate the interaction between bioactive compounds and biomolecules. In this paper, the novel asymmetric synthesis of lactisole derivatives with common photophores (benzophenone, azide and trifluoromethyldia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The conventional methods offered by the study showed that the 3-pyridyl-and 3-pyrimidyl-substituted 3trifluoromethyl-diaziridines were stable and could be readily oxidized into diazirine 27 with Ag2O-ether system. The novel asymmetric synthesis of trifluoromethyldiazirine-based lactisole derivatives 31 occurs as a result of the preparation of trifluoroacetyl modified on the aromatic ring of lactisole, which then introduces the diazirinyl three-membered ring on the trifluoroacetyl group [46]. However, to synthesize the starting material, advanced methods are required; since the 2-, 3-, and 4-trifluoroacetyl lactisole derivatives 32 (Scheme 3) need to consider the optical retention of the protected lactate counterpart, the conventional diazirine 31 construction via diaziridine 33 formation can be easily conducted, starting with oximation with hydroxylamine hydrochloride, tosylation for the hydroxyl group of oxime, diaziridine formation with liquid ammonia, and a final step of oxidation with activated MnO2 to obtain diazirine.…”
Section: Conventional Methods For Recent Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional methods offered by the study showed that the 3-pyridyl-and 3-pyrimidyl-substituted 3trifluoromethyl-diaziridines were stable and could be readily oxidized into diazirine 27 with Ag2O-ether system. The novel asymmetric synthesis of trifluoromethyldiazirine-based lactisole derivatives 31 occurs as a result of the preparation of trifluoroacetyl modified on the aromatic ring of lactisole, which then introduces the diazirinyl three-membered ring on the trifluoroacetyl group [46]. However, to synthesize the starting material, advanced methods are required; since the 2-, 3-, and 4-trifluoroacetyl lactisole derivatives 32 (Scheme 3) need to consider the optical retention of the protected lactate counterpart, the conventional diazirine 31 construction via diaziridine 33 formation can be easily conducted, starting with oximation with hydroxylamine hydrochloride, tosylation for the hydroxyl group of oxime, diaziridine formation with liquid ammonia, and a final step of oxidation with activated MnO2 to obtain diazirine.…”
Section: Conventional Methods For Recent Usesmentioning
confidence: 99%
“…However, to synthesize the starting material, advanced methods are required; since the 2-, 3-, and 4-trifluoroacetyl lactisole derivatives 32 (Scheme 3) need to consider the optical retention of the protected lactate counterpart, the conventional diazirine 31 construction via diaziridine 33 formation can be easily conducted, starting with oximation with hydroxylamine hydrochloride, tosylation for the hydroxyl group of oxime, diaziridine formation with liquid ammonia, and a final step of oxidation with activated MnO2 to obtain diazirine. The chiral center configuration was checked for every step, and asymmetric 2-, 3-, and 4-trifluoromethyldiazirine-based lactisole 31 were able The novel asymmetric synthesis of trifluoromethyldiazirine-based lactisole derivatives 31 occurs as a result of the preparation of trifluoroacetyl modified on the aromatic ring of lactisole, which then introduces the diazirinyl three-membered ring on the trifluoroacetyl group [46]. However, to synthesize the starting material, advanced methods are required; since the 2-, 3-, and 4-trifluoroacetyl lactisole derivatives 32 (Scheme 3) need to consider the optical retention of the protected lactate counterpart, the conventional diazirine 31 construction via diaziridine 33 formation can be easily conducted, starting with oximation with hydroxylamine hydrochloride, tosylation for the hydroxyl group of oxime, diaziridine formation with liquid ammonia, and a final step of oxidation with activated MnO 2 to obtain diazirine.…”
Section: Conventional Methods For Recent Usesmentioning
confidence: 99%
“…These results indicated that photoaffinity labeling with synthetic lactisole derivatives would be useful for the functional analysis of the sweet taste receptor ( Table 3 ). 84 …”
Section: Photoaffinity Probes For Inhibition (Negative Allosteric Mod...mentioning
confidence: 99%
“…21 Furthermore, the electrophilicity of halonium ions also allows the oxidative cleavage of 1,3-dithianes by using halogenation reagents including NBS (N-bromosuccinimide) 22 and NCS (N-chlorosuccinimide). 23,24 It is worth noting that various oxidative systems involving the use of iodine reagents such as NH4I/H2O2, 25 NaI/1,4-benzoquinone (BQ), 26 MeI, 27 I2/H2O2 28 and IBr 29 have also been used for this dethioacetalization process.…”
Section: Introductionmentioning
confidence: 99%